2022
DOI: 10.1177/03080226221125394
|View full text |Cite
|
Sign up to set email alerts
|

‘I left feeling different about myself’: What students learn on their first practice placement

Abstract: Introduction: With the inclusion of 40 hours of simulated practice education for UK occupational therapy students and the subsequent impact of the COVID-19 pandemic, universities have been exploring simulated placement opportunities. However, the evidence available to guide the development of such placements is sparse. This article presents the first stage of a grounded theory study that seeks to understand what students learn during the course of their first practice placement, with the intention of informing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…However, placements appear to offer more than just being a bridge between two worlds. Recent studies [16,91] of early-year placements in occupational therapy have shown that students perceive that they learn not only about the practices of the profession but about themselves and the service user journey. Perspectives of WIL amongst other professions also demonstrate a range of learning that occurs through placement.…”
Section: Discussionmentioning
confidence: 99%
“…However, placements appear to offer more than just being a bridge between two worlds. Recent studies [16,91] of early-year placements in occupational therapy have shown that students perceive that they learn not only about the practices of the profession but about themselves and the service user journey. Perspectives of WIL amongst other professions also demonstrate a range of learning that occurs through placement.…”
Section: Discussionmentioning
confidence: 99%
“…This current editorial reinforces the importance of the two levels of professional identity within the context of practice-based placement learning, to support the occupational therapists of tomorrow at a macro and micro level, from an individual employability point of view, and its impact on the future of the occupational therapy profession. A recent publication explored the student learning on a first practice placement (Grant et al, 2023) and reported four themes: learning about oneself, the profession, practices, and service users, which are all relevant for any practice-based placement learning. Alongside the macro professional identity development, a key element within each of the broader macro themes was the development of individual (micro) professional identities.…”
Section: Practice-based Placement Learning Professional Identities An...mentioning
confidence: 99%